PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, DAN LEVERAGE TERHADAP TARIF PAJAK EFEKTIF (Studi Kasus pada Sektor Energi yang Terdaftar di Bursa Efek Indonesia Periode 2019-2022) - Amanda, Nabila; Rakhmayani, Alfita (Jurnal Edueco, 2024)
Taxes are one of the biggest contributions for the country. Therefore, the government tries to maximize tax revenue to finance the country's development needs. However, this is contrary to the company's objectives, which want the company's effective tax rate to decrease further away from the statutory tax rate. This research aims to know the effect of firm size, profitability, and leverage on effective tax rate. The sample selection used a purposive sampling technique and obtained 52 samples. Data analysis using multiple linear regression analysis with the IBM SPSS version 26 program. The research results show that firm size has a positive effect on the effective tax rate, profitability and leverage have a negative effect on the effective tax rate. Simultaneously company size, profitability and leverage influence the effective tax rate.